Pengimplementasian Prinsip-Prinsip Good Corporate Governance Dalam Novel “After All This Time” Karya Ollyjayzee - Sisto Nugro Laksono; Rangga Pratama; Eva Dwi Kurniawan (Jurnal Manajemen Riset Inovasi, 2024)
Good Corporate Governance (GCG) is a structure and mechanism that regulates the management of a company so as to create long-term sustainable economic value for shareholders and stakeholders. In achieving company goals, GCG has the principles of transparancy, accountability, responsibility, independence and fairness. This research uses qualitative methods and hermeneutic methods The purpose of this research is to find out how the Track Construction Company implements the principles of Good Corporate Governance in the novel "After All This Time" by Ollyjayzee, in an effort to solve the problems faced in working on the Sindur toll road project. We hope that this research can provide lessons and additional information to readers. The results obtained are that by implementing the principles of Good Corporate Governance, the Track Construction Company can avoid the problems that hinder the work on the Sindur toll road project.